The Socioeconomic Impacts of COVID-19 on Households in Cambodia, Report No. 1 : Results from the High-Frequency Phone Survey of Households, Round 1 - Karamba, Wendy (World Bank, Washington, DC, 2021)
This brief summarizes the findings of the first round of a nationally representative high-frequency phone survey (HFPS) of households. The HFPS sample is drawn from the nationally representative living standard measurement study plus (LSMS+) implemented October to December 2019 by the National Institute of Statistics (NIS) with technical and financial support from the World Bank. The HFPS followed up with 1,364 households in LSMS+ with a phone number. The phone survey was successfully completed for 700 households for a response rate of 51 percent. Sampling weights were adjusted to ensure that the sample remains representative at the national and subnational level (urban and rural areas). The same households will be tracked over 10 months, with selected respondents - typically the household head - completing interviews every 8 weeks. Monitoring the well-being of households over time will improve understanding of the effects of, and household responses to the Coronavirus Disease 2019 (COVID-19) pandemic in near-real time.